Genetics of Hypertriglyceridemia - Dron, Jacqueline S.; Hegele, Robert A. (Frontiers in Endocrinology, 2020)
Hypertriglyceridemia, a commonly encountered phenotype in cardiovascular and metabolic clinics, is surprisingly complex. A range of genetic variants, from single-nucleotide variants to large-scale copy number variants, can lead to either the severe or mild-to-moderate forms of the disease. At the genetic level, severely elevated triglyceride levels resulting from familial chylomicronemia syndrome (FCS) are caused by homozygous or biallelic loss-of-function variants in LPL, APOC2, APOA5, LMF1 and GPIHBP1 genes. In contrast, susceptibility to multifactorial chylomicronemia (MCM), which has an estimated prevalence of 1 in 600 and is at least 50- to 100-times more common than FCS, results from two different types of genetic variants: 1) rare heterozygous variants (minor allele frequency <1%) with variable penetrance in the five causal genes for FCS; and 2) common variants (minor allele frequency >5%) whose individually small phenotypic effects are quantified using a polygenic score. There is indirect evidence of similar complex genetic predisposition in other clinical phenotypes that have a component of hypertriglyceridemia, such as combined hyperlipidemia and dysbetalipoproteinemia. Future considerations include: 1) evaluation of whether the specific type of genetic predisposition to hypertriglyceridemia affects medical decisions or long-term outcomes; and 2) searching for other genetic contributors, including the role of genome-wide polygenic scores, novel genes, nonlinear gene-gene or gene-environment interactions, and non-genomic mechanisms including epigenetics and mitochondrial DNA.